A comparison of Nuk presentation and Nuk redistribution to treat packing. Issue 2 (19th December 2018) - Milnes, Suzanne M.; Piazza, Cathleen C.; Ibañez, Vivian F.; Kozisek, Jennifer M.
Abstract : Children with feeding disorders may pack food when they lack the oral‐motor skills, the motivation, or both to swallow. Presenting bites on the tongue with a Nuk brush, or redistribution, replacing packed food on the tongue, are two treatments whose relative efficacy is untested. In the current study, we compared the effects of (a) presenting on an upright spoon, (b) presenting on a Nuk, and (c) redistributing with a Nuk on two product measures of swallowing, which we refer to as 15‐s and 30‐s mouth clean, for three children with feeding disorders. Nuk presentation produced the highest levels of 15‐s mouth clean relative to Nuk redistribution and upright‐spoon presentation across participants. Levels of 30‐s mouth clean were higher during Nuk presentation and Nuk redistribution relative to upright‐spoon presentation for two participants. We discuss the oral‐motor skills and motivational deficits that might account for the findings.